Evaluation of Clinical Graded Treatment of Acute Nonsuppurative Otitis Media in Children with Acute Upper Respiratory Tract Infection. (5th April 2021) - Meng, Wei; Huang, Dong-Dong; Li, Guang-Fei; Sun, Zi-Hui; He, Shuang-Ba
Abstract : Objective . To treat children with acute nonsuppurative otitis media induced by acute upper respiratory tract infection of varying severity and evaluate its therapeutic effects. Materials and Methods . Patients from the emergency department with acute nonsuppurative otitis media were followed up between September 2015 and December 2018. A total of 420 patients were classified into grades I to III according to tympanic membrane intactness and systemic reactions and treated according to grading. Results . Grade I patients showed no significant difference in the recovery of acute symptoms whether antibiotics are used or not. Grade II patients, after 3 months of follow-up, showed no tympanic membrane perforation, and 9 cases of binaural B-type children did not improve but were cured by operation. In grade III patients, after treatment for 4 hours in the experimental group 3, the earache subsided, 1 case had tympanic membrane perforation, and the patients recovered after 2 weeks (64/92) and after 3 months (28/92) of drug treatment. After treatment for 4 h in the control group 3, the earache eased, and 3 patients developed tympanic membrane perforation and were treated for 3 months. 4 binaural B-type children did not improve but recovered after surgical treatment. Conclusion . Grade I patients could be closely followed up by clinical observation. For anti-inflammatory patients with grade II disease, treatment has therapeutic significance. For patients with grade III, some patients still have TMP, but the use of cephalosporin third-generation drugs plus an appropriate amount of hormone therapy is effective in reducing symptoms and tympanic local reactions.